LIME: a new membrane Raft-associated adaptor protein involved in CD4 and CD8 coreceptor signaling - Brdicková, Nadezda; Brdicka, Tomás; Angelisová, Pavla; Horváth, Ondrej; Spicka, Jiri; Hilgert, Ivan; Paces, Jan; Simeoni, Luca; Kliche, Stefanie; Merten, Camilla; Schraven, Burkhart; Horejsí, Václav (The Journal of experimental medicine, 2003)
Lymphocyte membrane rafts contain molecules critical for immunoreceptor signaling. Here, we report identification of a new raft-associated adaptor protein LIME (Lck-interacting molecule) expressed predominantly in T lymphocytes. LIME becomes tyrosine phosphorylated after cross-linking of the CD4 or CD8 coreceptors. Phospho-LIME associates with the Src family kinase Lck and its negative regulator, Csk. Ectopic expression of LIME in Jurkat T cells results in an increase of Csk in lipid rafts, increased phosphorylation of Lck and higher Ca2+ response to CD3 stimulation. Thus, LIME appears to be involved in regulation of T cell activation by coreceptors.
Keywords: membránové mikrodomény; Phosphorylation; CD4 Antigens; antigeny CD4; Humans; C-terminální Src kinasa; fosforylace; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); Molecular Sequence Data; molekulární sekvence - údaje; src-Family Kinases; adaptorové proteiny vezikulární transportní; databáze proteinů; CSK Tyrosine-Protein Kinase; DNA, Complementary; lidé; tyrosinkinasa p56(lck), specifická pro lymfocyty; tyrosinkinasy; komplementární DNA; Adaptor Proteins, Vesicular Transport; Amino Acid Sequence; Protein-Tyrosine Kinases; Databases, Protein; antigeny CD8; CD8 Antigens; Membrane Microdomains; sekvence aminokyselin; skupina kinas odvozených od src-genu